FAKTOR-FAKTOR YANG MEMPENGARUHI FERTILITAS DI PROVINSI SUMATERA BARAT - Suci Fitri H; Idris Idris; Ariusni Ariusni (Universitas Negeri Padang, 2015)
The high fertility caused by people not running a government program that the family planning program (KB). This study aims to identify factors that affect fertility. See the phenomenon generally occurs, the problem can be formulated in this research is how the influence of neighborhood income level, maternal education, age at first marriage, and the use of family planning in West Sumatra. This study uses data Susenas 2013.Populasi research is the mother who gave birth to a child living in West Sumatra. Samples are taken 5528orang.Sampel spread in 19 regencies / cities in West Sumatra province both in urban areas and in pedesaan.Uji hypothesis is G test and the Wald test with 5% significance level. Based on research conducted seen that jointly RT level of income, maternal education, age at first marriage, and the use of family planning significant effect on fertility in West Sumatra.Keywords: fertility, income, materal education, age of first mating, kb